Prognostic Value of the Neo-Immunoscore in Renal Cell Carcinoma - Guo, Congfang; Zhao, Hua; Wang, Yu; Bai, Shuai; Yang, Zizhong; Wei, Feng; Ren, Xiubao (Frontiers in Oncology, 2019)
Objective: This study evaluated the prognostic value of the newly-built Immunoscore (neo-Immunoscore) in patients with renal cell carcinoma (RCC). Methods: Eighty-two patients with RCC were enrolled in this study. Their three- and five-year survival rates and overall survival (OS) were evaluated. The clinicopathologic data of the 82 patients were collected and analyzed. CD3, CD4, CD8, CD45RO, Foxp3, tumor necrosis factor receptor type II (TNFR2), programmed death ligand-1 (PD-L1), CD68, programmed death-1 (PD-1), cytokeratin (CK), and indoleamine 2,3-dioxygenase (IDO) were separated into two panels and stained using multiplex fluorescent immunohistochemistry methods. An immunologic prediction model of RCC patients, the neo-Immunoscore (neo-IS), was constructed using a Cox regression model. For the prognostic prediction of RCC, the neo-IS with the immunoscore (IS) proposed by the Society for Immunotherapy of Cancer (SITC) were compared by receiver operator characteristic (ROC) curve analysis. Survivals between the neo-ISlow and neo-IShigh groups were analyzed using the Kaplan–Meier method. Multivariate Cox regression survival analysis was applied to analyze independent indicators. Results: The Cox regression model allowed the establishment of a neo-IS based on three features: CD3+CT, CD4+Foxp3+CD45RO+CT, and CD8+PD-1+IM. Compared to that of the IS proposed by the SITC, the neo-IS obtained a better prediction. The three-year and five-year survival rates in neo-IShigh RCC patients were significantly higher than those in neo-ISlow RCC patients (94.7% vs. 77.4%, P = 0.035 and 94.7% vs. 64.5%, P = 0.002, respectively). The OS in the neo-ISlow group was significantly shorter than that in the neo-IShigh group (73 vs. 97 months, P = 0.000). In comparisons of the neo-IS with clinical pathological factors, we found that the risk stratification and neo-IS were independent factors for the prognosis of patients with RCC. Moreover, the overall survival rate of neo-IShigh RCC patients with low- and intermediate- risk was higher than that of neo-ISlow patients. Conclusion: The newly-constructed IS model more precisely predicted the survival of patients with RCC and may supplement the prognostic value of risk stratification.